1995
DOI: 10.1139/b95-079
|View full text |Cite
|
Sign up to set email alerts
|

Nutrient limitations in the northern pitcher plant Sarracenia purpurea

Abstract: The idea that carnivorous plants capture insects to supply limiting nutrients is often conjectured but rarely tested with fertilization trials or the construction of nutrient budgets. Accordingly, Sarracenia pupurea plants were analyzed for nitrogen and phosphorus after a 4-month fertilization of the pitchers with nitrogen, phosphorus, micronutrients, combinations thereof, and insect material. Neither the number of leaves produced in the same season nor average leaf mass differed significantly between treatmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
59
1

Year Published

1996
1996
2022
2022

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 60 publications
(64 citation statements)
references
References 10 publications
4
59
1
Order By: Relevance
“…Increased foliar concentrations of these elements as a result of digesting insect prey have been reported for Sarracenia spp. (Christensen 1976;Chapin and Pastor 1995), Pinguicula vulgaris (Aldenius et al 1983), and Drosera sp. (Chandler and Anderson 1976).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Increased foliar concentrations of these elements as a result of digesting insect prey have been reported for Sarracenia spp. (Christensen 1976;Chapin and Pastor 1995), Pinguicula vulgaris (Aldenius et al 1983), and Drosera sp. (Chandler and Anderson 1976).…”
Section: Discussionmentioning
confidence: 99%
“…However, while the benefits of prey capture are documented for other carnivorous plant families (Sarraceniaceae [Christensen 1976;Chapin and Pastor 1995], Lentibulariaceae [Aldenius et al 1983], Droseraceae [Chandler and Anderson 1976;Wilson 1985;Thum 1988;Schulze and Schulze 1990;Gibson 1991;Karlsson and Pate 1992] thes species to investigate this aspect of their biology. We explored this question by assessing the consequences of zero prey capture to N. rafflesiana in its natural habitat via analysis of pitcher production, tissue nutrient status, and foliar reflectance.…”
Section: Introductionmentioning
confidence: 99%
“…The study by Chapin and Pastor (1995) capensis during our experiment may directly be correlated to trap and absorption mechanisms. As well, in other studies, the supplementary nitrogen source had been added in different forms and, in many cases, with other nutrients, suggesting a possible link between combinations of nutrients being more effective (Hanslin and Karlsson 1996;Adamec 2002;Adamec 1997;Zamora et al 1997).…”
Section: Cultivation and Morphologymentioning
confidence: 77%
“…This indicates that D. capensis did not benefit in biomass from supplementary nitrogen as control plants grew apparently as well as those receiving supplementary nitrogen. Chapin and Pastor (1995) also showed that S. purpurea did not differ in terms of biomass as compared to the control when supplemented with an N~CI fertilizer into the pitchers. These results suggest three possibilities: 1) the concentration of N~CI was not high enough to show effective results; 2) the fertilizer N~CI is not effective in terms of biomass production and may require the presence and/or action of other nutrients which could lead to increased biomass or 3) the fertilizer N~CI is not readily taken up by the absorbing mechanisms found on the leaves of D. capensis.…”
Section: Cultivation and Morphologymentioning
confidence: 81%
See 1 more Smart Citation